Does stress at work make you gain weight? A two-year longitudinal study - Martial Berset; Norbert K Semmer; Achim Elfering; Nicola Jacobshagen; Laurenz L Meier (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: Research concerning the association between stress at work and body mass index (BMI) has mainly focused on two models (ie, job demand-control and effort-reward imbalance) as predictors and mostly been cross-sectional. The aim of our study is to extend previous research in two ways. First, social stressors - in the sense of social conflict and animosities at work - were included as an independent variable, arguing that they should be an especially promising predictor as they reflect a "social-evaluative threat". Second, a longitudinal design was employed with a two-year follow-up. In addition, the variables specified by the job demand-control model and the effort-reward imbalance model were assessed as well. METHODS: Participants comprised 72 employees (52 men, 20 women) from a Swiss service provider. Multiple regression analyses were used to predict BMI two years later with social stressors, effort-reward imbalance, demands, control, and the interaction of demands and control. Baseline BMI was controlled so that the dependent variable reflects the change in BMI over two years. RESULTS: Regression analyses revealed control and social stressors to be statistically significant predictors of follow-up BMI, while effort-reward imbalance was marginally significant. CONCLUSIONS: The results underscore the importance of social stressors and job control as predictors of stress-related impaired health.